PERLINDUNGAN HUKUM TENTANG JAMINAN SOSIAL BAGI TENAGA KERJA DI PURWA CARAKA MUSIC STUDIO SAMARINDA BERDASARKAN UNDANG-UNDANG NOMOR 24 TAHUN 2011 TENTANG BADAN PENYELENGGARA JAMINAN SOSIAL - Nur An Nisaa (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
AbstractProtection of the right to social security for workers is very important and necessary, especially when dealing with occupational risks even during the occurrence of work accidents. The problems examined in this study include 2 (two) things: first, what constitutes labor rights according to Law Number 40 of 2004 concerning the National Social Security System, Law Number 24 of 2011 concerning the Social Security Organizing Body and Law Number 13 of 2003 concerning Manpower. Second, how is the implementation of the right to labor social security at the Purwa Caraka Music Studio in Samarinda. The research method used in this writing is the Juridical-Empirical method with the fact approach method which is done by seeing firsthand the real situation at the research site, Purwa Caraka Music Studio (PCMS) Samarinda. The results of this study, the rights granted according to Law number 40 of 2004 concerning the National Social Security System, Law Number 24 of 2011 concerning the Social Security Organizing Agency is to provide social security in the form of work accident insurance programs, old age benefits, pension guarantees and death guarantees. Labor rights according to Law number 13 of 2003 concerning employment is to provide social health insurance for work health, decent wages, leave entitlements, etc. Then, the implementation of labor rights in Samarinda's PCMS is in accordance with applicable laws and regulations. As for workers who do not get social security because they are still on probation and when accidents occur, the form of protection provided is preventive protection by sending victims to clinics or hospitals and providing first aid kits on each floor and repressive protection measures by providing compensation treatment for workers who have had work accidents that have not been registered with the BPJS. The advice given by the writer first is that further research is needed to map the role of government, synchronize with other laws and regulations relating to the management of the social security system. Second, the Samarinda PCMS should further optimize work safety and health efforts for workers and workers should be registered on the first day of work. The government must also reinforce sanctions for companies that have not registered workers in accordance with applicable regulations. As well as providing information on the importance of occupational safety and health, as well as information on the existence of the Government's social security program, BPJS.